(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the clinical characteristics, imaging and lung lesions when patients inhale foreign objects into the airways. Methods: Case-series of 24 patients with foreign bodies in the airways. Results: The male:female ratio was 2:1. Age ranges from 11 - 71 years old, average 56.1 ± 15.8 years old. Common symptoms are cough, sputum (100%), fever (75.0%), difficulty breathing (70.8%), chest pain (45.8% and hemoptysis (25.0%). Size The average foreign body is 11.54 ± 2.7mm, the smallest is 6.5mm and the largest is 16.5mm. The most common types of foreign bodies are bones (62.5%), followed by nuts (20.8 %), the remaining less common are teeth, metal, bamboo toothpicks and pills (4.2%). The most common distance to carina is from 5-10mm, the closest distance is 3mm, the farthest is 15.5mm, average 6.4 ± 2.9mm. Time from inhaling a foreign object to the time that patient comes for examination and treatment is 1 day at the earliest, 135 days at the latest, average 19.7 ± 31.3 days. The most common lesions shown on CT scan are fibrosis and bronchial narrowing of the segment with foreign bodies (37.5%), followed by bronchial wall thickening and increased mucus secretion (25.0%). The most common complications are pneumonia, lung parenchymal consolidation and distal lung collapse (70.8%). Main treatment is using flexible bronchoscopy to remove foreign objects (91.7%). Tthere were 2 cases of lung lobectomy to treat patients. After the procedure and surgery, the patients progressed well, with an average hospital stay of 12.9 ± 6.7 days. Conclusion: Computed tomography is the best tool to diagnose airway foreign bodies. CT scan accurately determines the cause, size, location and accompanying abnormalities. From there, we provide safe, quick and effective treatment methods for patients.